Rates of glucose utilization and glucogenesis in rats in the basal state induced by halothane anaesthesia. - Heath, D; Frayn, K; Rose, J (1977)
1. Rates and rate coefficients of glucose utilization and replacement were determined with [5-3H]- and [U-14C]-glucose in rats starved for 24h, either conscious or under halothane anaesthesia, in a thermoneutral environment. Plasma insulin concentrations were also measured. 2. Halothane anaesthesia decreased the turnover rate by 20%, which was similar to previously reported decreases in metabolic rates caused by natural sleep. 3. Fractional recycling of glucose carbon was little affected by halothane. 4. Comparison of values in one rat with those in another, among both conscious rats and those under halothane anaesthesia, showed that rate coefficients were inversely correlated with plasma glucose concentrations. 5. These findings indicated that halothane, in the concentration used (1.25%, v/v), had little specific effect on glucose metabolism. 6. Although equilibrium plasma glucose concentrations in different rats under halothane were widely different (4-8 mmol/l) the rates of utilization were very similar (2.5-3.1 micronmol/min per 100 g), indicating that these rates were determined by the production of glucose from gluconeogenic precursors released by basal metabolism, the rate of which is necessarily similar in different rats. 7. Among rats under halothane anaesthesia plasma insulin concentrations were negatively correlated with rate coefficients, showing that the differences between rate coefficients were mostly accounted for by differences between rats in tissue sensitivities to insulin. Thus in each 24h-starved rat, sleeping or resting, the main regulators of the plasma glucose concentrations were the rate of supply of gluconeogenic substrates from energy metabolism and the intrinsic sensitivity of the tissues to insulin. 8. We found that a commonly used deionization method of purifying glucose for determination of its specific radioactivity was inadequate.